ANALYZING THE POWER OF WORDS IN BEYONCÉ’S INSTAGRAM COMMENTS - Safira Fahroji; Shanty AYPS Duwila; Surya Priyambudi (Pusat Studi GESI - UWP, 2025)
This study examines speech acts and hate speech in the comment sections of Beyoncé's Instagram. It focuses on the types of hate speech directed at her. Using a qualitative approach, the research explores how hate speech functions as speech acts, especially in shaping emotional and psychological impacts. Thirty comments were collected from Beyoncé's most commented posts over six months (September 2024–February 2025), particularly during negative public controversies. Data collection involved locating her account, selecting relevant posts, reviewing comments for hate speech, and capturing screenshots. The analysis followed several steps: compiling and identifying comments, categorizing hate speech types, analyzing them with hate speech theory, interpreting the results, and concluding the findings. The study identified four main types of hate speech: insults, provocations, defamation, and offensive behavior. Results show that hate speech, produces real emotional, and psychological harm. These findings highlight the serious impact of online hate and the importance of addressing harmful language in digital spaces.